Compartmentalized Reconstitution of Post-squalene Pathway for 7-Dehydrocholesterol Overproduction in Saccharomyces cerevisiae - Guo, Xiao-Jing; Yao, Ming-Dong; Xiao, Wen-Hai; Wang, Ying; Zhao, Guang-Rong; Yuan, Ying-Jin (Frontiers in Microbiology, 2021)
7-Dehydrocholesterol (7-DHC) is the direct precursor to manufacture vitamin D3. Our previous study has achieved 7-DHC synthesis in Saccharomyces cerevisiae based on the endogenous post-squalene pathway. However, the distribution of post-squalene enzymes between the endoplasmic reticulum (ER) and lipid bodies (LD) might raise difficulties for ERG proteins to catalyze and deliver sterol intermediates, resulting in unbalanced metabolic flow and low product yield. Herein, we intended to rearrange the subcellular location of post-squalene enzymes to alleviate metabolic bottleneck and boost 7-DHC production. After identifying the location of DHCR24 (C-24 reductase, the only heterologous protein for 7-DHC biosynthesis) on ER, all the ER-located enzymes were grouped into four modules: ERG1/11/24, ERG25/26/27, ERG2/3, and DHCR24. These modules attempted to be overexpressed either on ER or on LDs. As a result, expression of LD-targeted DHCR24 and ER-located ERG1/11/24 could promote the conversion efficiency among the sterol intermediates to 7-DHC, while locating module ERG2/3 into LDs improved the whole metabolic flux of the post-squalene pathway. Coexpressing LD-targeted ERG2/3 and DHCR24 (generating strain SyBE_Sc01250035) improved 7-DHC production from 187.7 to 308.2 mg/L at shake-flask level. Further expressing ER-targeted module ERG1/11/24 in strain SyBE_Sc01250035 dramatically reduced squalene accumulation from 620.2 mg/L to the lowest level (by 93.8%) as well as improved 7-DHC production to the highest level (to 342.2 mg/L). Then targeting module ERG25/26/27 to LDs further increased 7-DHC titer to 360.6 mg/L, which is the highest shake-flask level production for 7-DHC ever reported. Our study not only proposes and further proves the concept of pathway compartmentalized reconstitution to regulate metabolic flux but also provides a promising chassis to produce other steroidal compounds through the post-squalene pathway.